تمثال ملكى جماعى يمثل الملك (سنوسرت الأول –امنمحات الأول – منتوحتب الثانى –سنفرو؟) المتحف المصرى الكبير GEM1334 A Royal Group Statue Representing the king (Senusret I - Amenemhat I - Mentuhotep II - Sneferu?). The Grand Egyptian Museum GEM1334- SR3/9796. - Reham Sayed Ali Abd Rabbo (Journal of General Union of Arab Archaeologists, 2023)
AR يتناول هذا البحث تمثالاً ملكياً جماعياً رباعياً يمثل الملك ( سنوسرت الأول ،أمنمحات الأول ، منتوحتب الثانى، سنفرو؟)، من الحجر الرملى وهو فى فى حالة سيئة ، محفوظ حاليا فى المتحف المصرى الكبير GEM1334 ، وقد عثر عليه فى معبد سرابيط الخادم للإلهة حتحور(جنوب سيناء) صالة الأعمدة، والتمثالُ إهداء من الملك "سنوسرت الأول" لإحياء ذكرى الأسلاف وهو عبارة عن تمثال ملكى لأربعة ملوك فى وضع الجلوس مستندين على ركبهم بجوار بعضهم البعض، وأيديهم مفرودة على مائدة قرابين والرؤوس مفقودة، وتتمحور إشكالية البحث حول ماهية التمثال الأخير، إذ نتيجة حالة التمثالُ فُقد الاسم الأخير للملك وتعددت الآراء حول ما إذا كان يمثل الملك سنفرو أم يُمثل الملك منتوحتب الثالث . EN The research studies a quartet royal statue representing the king (Senusret I - Amenemhat I - Mentuhotep II - and Sneferu?). It was made out of Sandstone, in poor condition, and currently preserved in the Grand Egyptian Museum GEM1334-SR3/9796. It was discovered in the pillared hall of Hathor temple at Serabit al-Khadim (South Sinai). The statue is a gift from King "Senusret the First" to commemorate the ancestors. It is a royal statue of four kings in a sitting position, kneeling next to each other, with their hands spread out on an offering table, and their heads are missed. The condition of the final statue is a matter of concern due to its poor condition, its name was missed, and there were many opinions about whether it represented King Sneferu or King Mentuhotep III.